CHILD FRIENDLY CITY DEVELOPMENT MODEL USING A SOCIOLOGICAL APPROACH IN KENDARI CITY - Dewi Anggraini; La Ode Monto Bantu; La Ode Muhammad Elwan; M. Najib Husain (Halu Oleo University, 2024)
Kendari City faces various challenges in creating a suitable environment for children's development, including issues of infrastructure, security, as well as educational and cultural aspects. The synergy between government and society is very important to realize positive change and an environment that supports optimal child growth. This research uses a qualitative descriptive method with an ethnographic study. The research results show that the city components that support Kendari City as a child-friendly city include the living environment, community environment, school environment, play environment, transportation services and children's health services. The supporting and inhibiting factors for Kendari as a child-friendly city consist of internal factors from the policy-implementing environment and external factors from outside the policy-implementing environment.